Pengaruh Penggunaan E-commerce, Digital Influencer, dan Efikasi Diri terhadap Perilaku Berwirausaha - Sherla Pramesti; Norida Canda Sakti (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
Indonesia continues to experience a high unemployment rate, primarily due to limited job opportunities. This research seeks to enhance young students' initiatives by leveraging technology and fostering individual self-confidence. The objective is to explore the roles of e-commerce, digital influencers, and self-efficacy in shaping students' entrepreneurial behavior. A quantitative method was employed using a causal research design and multiple linear regression analysis, supported by IBM SPSS Software Version 25. The study sampled 95 eleventh-grade students from SMAN 18 Surabaya. The findings indicate that e-commerce, digital influencers, and self-efficacy collectively influence entrepreneurial behavior. Among these, digital influencers significantly impact entrepreneurial behavior on an individual basis. Self-efficacy also demonstrates a positive influence, whereas e-commerce alone does not show a direct effect. As a result, schools are encouraged to incorporate e-commerce education to introduce students to modern marketing strategies.